Orbital solitary fibrous tumor in a commercial airline pilot - Altınbaş, Munise; Özpınar, Ayşe; Akbaba, Müslime; Aşık Nacaroğlu, Şenay; Sargolzaeimoghaddam, Mohammad; Sargolzaeimoghaddam, Maral (My University, 2024)
BACKGROUND: In the literature, central serous retinopathy (CSR) accompanying solitary fibrous tumors (SFT) in a pilot has not been reported. In airline pilots, mass effect-related symptoms such as diplopia, ptosis, etc., seen with orbital tumors may endanger flight safety. CASE REPORT: A 62-yr-old male commercial airline pilot presented with blurred vision in the right eye. He had been receiving treatment for 2 mo because of CSR. His visual acuity was 10/20 in the right eye and 20/20 in the left. During examination, ptosis and exophthalmos were noticed in the right eye. Ocular movements were free in all cardinal directions and there was downward displacement in the right eye. There was no diplopia. Magnetic resonance imaging revealed a 1.5-to 2-cm well-defined contrast-enhancing mass in the lateral extraconal orbit. His medical flight certificate was suspended for 3 mo due to decreased visual acuity and superior visual defect. Superior orbitotomy was performed without any complication. Ptosis and CSR had regressed 1 wk after surgery. All systemic and ophthalmological examinations met aviation medical certificate requirements. He returned to flight on the condition of being checked every 3 mo. At the 1-yr follow-up, there was no sign of recurrences of SFT or CSR. DISCUSSION: SFTs are slow-growing neoplasms that can manifest symptoms related to mass effect. In the current literature, there are no reported cases of the coexistence of orbital SFT and CSR or pilots able to resume flight duties only 1 wk after a successful orbitotomy and tumor resection surgery.
Keywords: Central Serous Retinopathy; Commercial Airline Pilot; Orbital Solitary Fibrous Tumor